2011
DOI: 10.5539/ass.v7n8p173
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Ethics as Moral Substance in the Context of Corporate Governance

Abstract: The Corporate Governance guidelines, rules and regulations were introduced to guide corporations towards good governance practices. However, there seem to be contradicting events that projected otherwise. The series of corporate scandals seems to be giving the impression that there is something lacking in the present corporation governance practices among the corporations, in particular, the public listed companies. Several opinions were gathered in answering this lacuna and the outcome seems to pin point to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Empirical evidence from previous studies has emphasized the important relationship of ethics in corporate governance. Othman & Rahman (2011) prove that ethics plays an important and significant role in corporate governance. They point out that ethical positions (independent bodies and whistleblowers), ethical principles (corporate philosophy) and ethical structure (ethical reporting and code of ethics) are important requirements for governance practices.…”
Section: Business Ethics and Its Relation To Good Corporate Governancementioning
confidence: 99%
See 2 more Smart Citations
“…Empirical evidence from previous studies has emphasized the important relationship of ethics in corporate governance. Othman & Rahman (2011) prove that ethics plays an important and significant role in corporate governance. They point out that ethical positions (independent bodies and whistleblowers), ethical principles (corporate philosophy) and ethical structure (ethical reporting and code of ethics) are important requirements for governance practices.…”
Section: Business Ethics and Its Relation To Good Corporate Governancementioning
confidence: 99%
“…Several previous studies have emphasized the important role of ethics in corporate governance (El-Kassar, Messarra & Elgammal, 2015;Othman & Rahman, 2011;Othman, Rahman & Shamsudin, 2012). In Malaysia, Othman & Rahman (2011) examined the role of ethics in corporate governance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joseph et al (2019, p. 112) highlighted that ethics principles are “preached but may not be practiced sincerely by professionals and employees.” Therefore, the value of ethics should be embedded into the companies’ culture and embraced by the employees (Abidin et al , 2017). The culture can be embedded internally through employees and externally through the distribution of the companies’ code of ethics to the relevant party (Othman and Rahman, 2010). KPMG (2014) in its survey revealed that the most common factors that contributed to unethical behavior are poor communication of the organization’s values or code of ethics or code of conduct, poor examples shown by senior management and poor ethical culture within the organization, as supported by Abidin et al (2020).…”
Section: Ethical Issues Practices and Communicationmentioning
confidence: 99%
“…A study by Zam et al (2014) highlighted that one of the factors that encourage fraud commission is weak ethical culture and poor corporate governance. An earlier study by Othman and Rahman (2010) through interviews with key players of corporate governance in Malaysia and companies revealed that several ethical dimensions such as ethical leadership, integration of ethical culture, and established corporate value stimulate corporate governance practices.…”
Section: Ethical Issues Practices and Communicationmentioning
confidence: 99%